Analisis Fonemik Dan Sintaksis Pada Anak Usia 5-6 Tahun di TK Qurrota A’yun 01 Kota Pekalongan - Anna Diana Shanty; Anita Chandra Dewi (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
This study discusses the acquisition of phonemes and syntax in children aged 5-6 years, with a qualitative descriptive approach and tries to describe the phonemes and syntax of children who appear when reading a picture story book. The data mining carried out by researchers by observation, interviews and documentation. The results obtained 1) in the semantics of almost all children's utterances contain denotative meanings, there are also sentences that appear with connotative meanings, 2) children replace the sounds of several consonants, namely l and w with the aim of making it easier to pronounce. At the age of 5 years, the phonemes / o/ and / h / are released and there is a change in the phonemes / r / so / l /, /l/ becomes /w/, /g/ becomes d, /k/ becomes /t/, /nga / so / na/, / f/ becomes /p/, /s/ becomes / t/, /j/ becomes /d/, /z/ becomes / d/, /l/ becomes / w/. And there is also the release of some consonants in order to make it easier to pronounce such as / shampoo / become /tamas/. And for the syntax, children cannot identify the time of events such as today, tomorrow or yesterday. In stringing words into SPOK sentences, it still needs a lot of practice, especially exploring more children's vocabulary, practicing children to answer questions, of course educators using open sentences. Keywords: phonemic, syntax, storytelling References Alfatihaturrohmah, A., Mayangsari, D., & Karim, M. B. (2018). Kemampuan Berbicara Anak Usia 5-6 Tahun di TK X Kamal. Jurnal PG-PAUD Trunojoyo : Jurnal Pendidikan Dan Pembelajaran Anak Usia Dini, 5(2), 101–109. https://doi.org/10.21107/pgpaudtrunojoyo.v5i2.4885 Allen, dan Marotz. (2010). Profil perkembangan anak. Jakarta : PT Indexs. Arifal Aris, A. (t.thn.). Pengembangan Kemampuan Berbahasa Melalui Metode Cerita Dengan Membacakan Buku Cerita bermedia gambar pada anak Pra . Jurnal Keperawatan Kesehatan. Arifuddin. (2010). Neuropsikolinguistik. Jakarta: Raja Grafindo Persada. Christianti, M. (2015). KAJIAN LITERATUR PERKEMBANGAN PENGETAHUAN FONETIK PADA ANAK USIA DINI. Jurnal Pendidikan Anak, 4(1), Article 1. https://doi.org/10.21831/jpa.v4i1.12339 Dardjowidjojo, Soenjono. (2016). Psikolinguistik: Pengantar Pemahaman Bahasa Manusia. Jakarta: Yayasan Pustaka Obor Indonesia. Fitriyyah, D. (2016). Membangun Karakter Anak Melalui Dongeng. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 1(1), 1–10. hariyanti, hariyanti. (2019). Meningkatkan Kemampuan Bahasa Ekspresif Anak Melalui Metode Bercerita Menggunakan Media Boneka Jari. Jurnal Pelita PAUD, 3(2). http://jurnal.upmk.ac.id/ index.php/ pelitapaud/ article/ view/520 Huliyah, M. (2016). Hakikat Pendidikan Anak Usia Dini. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71. Imroatun, I. (2017). Media Belajar Bigbook Bagi Pengembangan Baca Nyaring Anak Usia Dini. Prosiding Seminar Nasional Pembelajaran Baca, Tulis, Dan Hitung Tingkat Permulaan Bagi Anak Usia Dini, 119–127. https://www.academia.edu/39959344/MEDIA_BELAJAR_BIGBOOK_BAGI_PENGEMBANGAN_BACA_NYARING_ANAK_USIA_DINI M, M. (2019). PENGEMBANGAN NILAI MORAL ANAK MELALUI METODE BERCERITA PADA KELOMPOK B DI TK PEMBINA KOTA KENDARI. Gema Pendidikan, 26(1), 97–112. https://doi.org/10.36709/gapend.v26i1.6779 Ma’isyah, N. (2018). Pengembangan Modul Membaca Lancar Pokok Bahasan Lingkungan Yang Bernuansa Kontekstual. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(2), 137–146. Moleong, Lexy. (2002). Metode Penelitian Kualitatif, Bandung : CV. Remaja Munirah, M. (2018). PRINSIP-PRINSIP BELAJAR DAN PEMBELAJARAN (Perhatian dan Motivasi, Keaktifan, Keterlibatan Langsung, Pengulangan, Tantangan dan Perbedaan Individu). AULADUNA: Jurnal Pendidikan Dasar Islam, 5(1), 116–125. https://doi.org/10.24252/ auladuna.v5i1a10.2018 Munirah, M. (2018). PRINSIP-PRINSIP BELAJAR DAN PEMBELAJARAN (Perhatian dan Motivasi, Keaktifan, Keterlibatan Langsung, Pengulangan, Tantangan dan Perbedaan Individu). AULADUNA: Jurnal Pendidikan Dasar Islam, 5(1), 116–125. https://doi.org/10.24252/ auladuna.v5i1a10.2018 Rusniah. (2017). Meningkatkan Perkembangan Bahasa Indonesia Anak Usia Dini Melalui Penggunaan Metode Bercerita pada Kelompok A Di TK Malahayati Nuehen Tahun Pelajaran 2016/2017 . Jurnal Edukasi Wulandari D.I. (2018). Pemerolehan bahasa Indonesia anak usia 3-5 tahun di PAUD Lestari desa Blimbing kecamatan Paciran kabupaten Lamongan. Lingua Franca Jurnal Bahasa Sastra dan Pengajarannya. Zakaria M, S. I. (t.thn.). Perolehan Fonem Bahasa Ibu Anak Usia 2,6 Tahun ,Study kasus "Rasyid Hidayat " : Acquisition of Phonemes For Mother Tongue Children Aged 2,6 Years: A Case Study in : "Rasyid Hidayat" . Jurnal Bastrindo 100 - 10.